The law of war and peace : a gender analysis. Volume 1 - Heathcote, Gina; Jones, Emily; Labenski, Sheri; Bertotti, Sara (London, England : Zed Books, 2021)
The first extended legal studies analysis of the interplay between gender, conflict and international law, applying an intersectional, decolonial approach to gendered experiences of war.
Cover -- Contents -- Author Biographies -- Table of Cases -- Abbreviations -- Introduction -- Chapter 1 Collective Security -- Chapter 2 Unilateral force -- Chapter 3 COUNTERING terrorism -- Chapter 4 International humanitarian law of armed conflict -- Chapter 5 International criminal law -- Bibliography -- Index.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: War (International law); Women and war; Gender studies, gender groups; Electronic books